AN APPROACH TO SOLUTION FOR THE PURSUIT PROBLEM UNDER LACK OF KNOWLEDGE - Demir, Ibrahim (YILDIZ TECHNICAL UNIV, 2005)
In this article, under lack of knowledge the linear differential games are analyzed and a new solution method is constructed. At this work, terminal set for linear differential games are taken as cylindrical set and in this set the possibility of finishing game is shown.
Keywords: Differential games; Pursuit problems; Lack of knowledge; Engineering